ANALISIS WACANA LIRIK LAGU DAERAH KUTAI “BUAH BOLOK” DAN “NASI BAKEPOR” - Nur Bety (Kantor Bahasa Kalimantan Timur, 2019)
Song is a means of conveying one's expression. This paper will describe the grammatical aspects and lexical aspects in the lyrics of the song